EXPLORING THE INFLUENCE OF SUBJECTIVE NORMS, PERCEIVED BEHAVIORAL CONTROL, AND ATTITUDES ON TRUST IN ISLAMIC BANKS: AN EMPIRICAL ANALYSIS - Muhammad Adeel; Muhammad Umer Quddoos; Arslan Ahmad Siddiqi; Mazhar Iqbal (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Purpose In today’s business world, customer trust is key to managing a business. This study aims to examine the impact of three constructs of the theory of planned behavior including Subjective Norms, Perceived Behavior Control, and Attitude on trust in Islamic Banks (IBs). Design/Methodology/Approach We collected data through an online questionnaire. Judgmental/purposive sampling was used. We employed 164 responses in the analysis. Partial Least Square Equation Modeling (PLS-SEM) was employed to analyze the data for which Smart PLS software version 4 was used. Findings The results show that Subjective Norms, Perceived Behavior Control, and Attitude positively and significantly impact Trust in Islamic Banks. Research Limitation/Implication We focused on Subjective Norms, Perceived Behavior Control, and Attitude only. Moreover, this study was conducted in a single country. Therefore, for future research, we suggest conducting a cross-country analysis employing other antecedents of trust. Practical Implications Based on research findings, Islamic Bank managers have input on how to improve Trust in IBs. They can revamp marketing strategies accordingly. Originality/Value This study is an attempt to study Subjective Norms, Perceived Behavior Control, and Attitude as antecedents of Trust in IBs.